2021
DOI: 10.1186/s12939-021-01415-4
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the use of percutaneous coronary interventions among older patients with acute coronary syndromes: a multilevel study in Fukuoka, Japan

Abstract: Background Variation in health care delivery among regions and hospitals has been observed worldwide and reported to have resulted in health inequalities. Regional variation of percutaneous coronary intervention (PCI) was previously reported in Japan. This study aimed to assess the small-area and hospital-level variations and to examine the influence of patient and hospital characteristics on the use of PCI. Methods Data provided by the Fukuoka Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…However, the invasive procedure rate for AMI among patients with dementia was remarkably lower compared with previous research on PCI use. [40][41][42] The reasons for this low rate may include complex comorbidities, uncertain benefits and insufficient guidelines, resulting in patients' conservative preferences for treatment and physicians' difficulty in making judgements and recommendations for these patients. Our findings showed that patients undergoing invasive procedures usually had fewer comorbidities but were prescribed more drugs, compared with patients who did not undergo these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…However, the invasive procedure rate for AMI among patients with dementia was remarkably lower compared with previous research on PCI use. [40][41][42] The reasons for this low rate may include complex comorbidities, uncertain benefits and insufficient guidelines, resulting in patients' conservative preferences for treatment and physicians' difficulty in making judgements and recommendations for these patients. Our findings showed that patients undergoing invasive procedures usually had fewer comorbidities but were prescribed more drugs, compared with patients who did not undergo these procedures.…”
Section: Discussionmentioning
confidence: 99%